Digestion, Absorption, Bioavailability and Clinical Efficacy of Collagen Supplements - Reilly, David M.; Sui, Cong; Kynaston, Liane; Laceby, Darcy (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
Historically, ageing was considered an inevitable process, with accumulating loss of function that occurred with increasing time span. Anti-ageing, in this context, primarily focuses on prevention and repair mechanisms designed to limit cell, tissue and skin damage and/or attempt to repair damaged components. In recent years, the concept being developed through both drug, dietary and lifestyle interventions is that of the “Healthspan”, which focuses on living for longer in a state of wellbeing, free of significant illness or disease. The dietary requirements contributing to improved Healthspan include optimised macronutrients (protein, sugar, fat) and micronutrients (vitamins, minerals, natural extracts). Collagen is the main protein in the human body (approximately 30% dry weight), and maintaining the structural and functional integrity of collagen in the body will be an important factor in the extended Healthspan of people. Collagen fibres in the extracellular matrix, in combination with elastin and glycosaminoglycans, are the key determinants of elasticity, wrinkles and skin hydration. Collagen levels in skin decline with age, and this is due to intrinsic factors (e.g., genetics, hormones, mitochondrial deficits) and extrinsic factors (e.g., UV-radiation, pollution). In ageing skin, the content of collagen typically decreases by about 1.0-1.5% per year. Hydrolysed collagen supplements are a popular bioactive, proven to protect and repair the skin, maintaining collagen in an optimal state of functionality. At Absolute Collagen, we commissioned an independent, randomised, double-blind, placebo-controlled study designed to evaluate the efficacy of a supplement containing hydrolysed collagen and vitamin C on skin ageing. After consumption of the supplement for 12 weeks, skin hydration was increased 13.8% (p<0.01), R2 elasticity index was increased 22.7% (p<0.01), and Rz profilometry index showed a decrease in fine lines and wrinkles 19.6% (p<0.01). This chapter will briefly outline the key processes which determine the value of hydrolysed collagen as an antiaging supplement, including mechanistic processes (digestion, absorption), bioavailability and clinical efficacy (as measured using biophysics, expert visual assessment and self-perception).